Aleurochiton orientalis Danzig, 1966 (Hemiptera: Aleyrodidae), newly recorded from China, with a key to puparia of all described Aleurochiton species - Wang, Ji-Rui; Martin, Jon H.; Xu, Zhi-Hong; Du, Yu-Zhou (Entomologica Fennica, 2016)
The genus Aleurochiton Tullgren (1907) is here newly recorded from China as A. orientalis Danzig (1966). It was collected from Acer mono Maxim (Sapindales: Aceraceae) in Shaanxi Province, but was originally described from the Russian Far East (Southern Primor’ye) by Danzig (1966). The puparial morphology of A. orientalis is here illustrated by line art, photomicrographs and scanning electron microscope (SEM) photographs. An identification key to the all five described Aleurochiton species is provided.